Phosphorus Compartmentalization on the Cellular Level of Douglas Fir Root as Affected by Mn Toxicity: A Synchrotron-Based FTIR Approach. Issue 5 (11th July 2012) - Dučić Dučić, Tanja Tanja; Thieme Thieme, Jürgen Jürgen; Polle Polle, Andrea Andrea
Abstract : We investigated distribution of phosphorus under manganese toxicity in different tissues of 10  μ m thin-root cross-section of Douglas fir (DF) ( Pseudotsuga menziesii ) seedlings by using synchrotron-based Fourier transform infrared microscopy (SR-FTIR) as a chemically sensitive imaging method. Manganese is an essential micronutrient in all organisms but may become toxic when present in excess. We found previously that DF variety glauca (DFG) and variety menziesii (DFM) differed in phosphorus uptake, subcellular localization, transport and tissue allocation, as an effect of manganese toxicity. To address the role of P in seedling tolerance under Mn toxicity, we determined P allocation in different root tissues. In DFG, but not in DFV, the P concentration was kept at a constant level even under Mn toxicity. Earlier X-ray microanalysis showed Mn accumulation in epidermal and cortical cells of both varieties after Mn treatment, suggesting that the root endodermis was a barrier for Mn to protect the vascular system and shoot from high Mn, with possible role of P ameliorations. Here, we discuss the potential role of P in Mn compartmentalization and toxicity tolerance in two different varieties.